1997
DOI: 10.1109/2944.649548
|View full text |Cite
|
Sign up to set email alerts
|

230 mW of blue light from a thulium-doped upconversion fiber laser

Abstract: We demonstrate a powerful diode-pumped blue laser source, consisting of a 7W diode at 807nm that pumps a Nd:YAG laser giving 1.6W with good beam quality at 1123nm, and a thulium-doped upconversion fiber laser. The maximum output power achieved at 481nm is 230mW. We also describe the behavior of a reversible loss which is generated in the fluoride fiber during high power operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(27 citation statements)
references
References 12 publications
0
26
0
1
Order By: Relevance
“…In 1997, Zellmer et al [148] demonstrated a 100 mW all fiber laser system in which a Tm 3+ /Yb 3+ -doped ZBLAN fiber was pumped with a 2.8 W diode pumped Nd 3+ -doped silica fiber laser at 1065 nm. In the same year, Paschotta et al [129] achieved the highest output (230 mW) of 480 nm light from a Tm 3+ -doped ZBLAN fiber laser pumped by a 1.6 W Nd:YAG laser at 1123 nm. However, the fiber laser performance degraded quickly at high-power operation.…”
Section: Upconversion Er 3+ -Doped Zblan Fiber Lasers the Partial Enmentioning
confidence: 99%
“…In 1997, Zellmer et al [148] demonstrated a 100 mW all fiber laser system in which a Tm 3+ /Yb 3+ -doped ZBLAN fiber was pumped with a 2.8 W diode pumped Nd 3+ -doped silica fiber laser at 1065 nm. In the same year, Paschotta et al [129] achieved the highest output (230 mW) of 480 nm light from a Tm 3+ -doped ZBLAN fiber laser pumped by a 1.6 W Nd:YAG laser at 1123 nm. However, the fiber laser performance degraded quickly at high-power operation.…”
Section: Upconversion Er 3+ -Doped Zblan Fiber Lasers the Partial Enmentioning
confidence: 99%
“…Incorporating the fluoride host in an optical waveguide geometry can also offer low thresholds and high efficiencies, increasing the potential for continuous wave (CW) operation at room temperature and at relatively high power levels. This has been demonstrated most effectively with ZBLAN optical fibers [3]- [5].…”
Section: Introductionmentioning
confidence: 99%
“…In that sense, lanthanide ions are among the most studied dopants and particularly Tm 3+ is notable due to the wide range of fields in which its emissions are potentially applicable. This is partly thanks to the energetic position of its infrared emissions, interesting in optical communications, surgery or remote sensing, and partly thanks to the resonant character of many transitions that allow efficient up-conversion processes that generates visible frequencies [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%